Inhibition of GAPDH aggregation as a potential treatment for acute ischemic stroke - Masanori Itakura; Takeya Kubo; Akihiro Kaneshige; Masatoshi Nakatsuji; Naoki Harada; Ryoichi Yamaji; Takatoshi Hikida; Takashi Inui; Hidemitsu Nakajima (iScience)
Summary: Neuronal death in acute ischemic stroke (AIS) is largely caused by the neurotoxic mechanism of oxidative/nitrosative stress, which is responsible for ischemia-reperfusion injury. Glyceraldehyde-3-phosphate dehydrogenase (GAPDH) is a multifunctional protein that mediates cell death under oxidative/nitrosative stress. The active site of GAPDH, residue cysteine-152 (Cys-152), is oxidized and forms intermolecular disulfide bonds that induce GAPDH aggregation, which causes mitochondrial dysfunction and eventually leads to cell death. A GAPDH-C152A mutant dominant-negatively suppresses GAPDH aggregation. Herein, we report that neuron-specific expression of GAPDH-C152A in conditional transgenic mice decreased GAPDH aggregation and brain damage induced by ischemia-reperfusion injury in an AIS mouse model. Furthermore, GAPDH aggregation inhibitor peptide-17, developed by our peptide-screening-methods, ameliorated brain infarction and neurological deficits, even after 6 h of reperfusion. These findings suggest that inhibition of GAPDH aggregation may be a potential therapeutic target for AIS. Further efforts are warranted to translate these findings to treatment with AIS.